Enterococcus faecalis manganese exporter MntE alleviates manganese toxicity and is required for mouse gastrointestinal colonization - Lam, Ling Ning (2021)
Bacterial pathogens encounter a variety of nutritional environments in the human host, including nutrient metal restriction and overload. Uptake of manganese (Mn) is essential for Enterococcus faecalis growth and virulence; however, it is not known how this organism prevents Mn toxicity. In this study, we examine the role of the highly conserved MntE transporter in E. faecalis Mn homeostasis and virulence. We show that inactivation of mntE results in growth restriction in the presence of excess Mn, but not other metals, demonstrating its specific role in Mn detoxification. Upon growth in the presence of excess Mn, an mntE mutant accumulates intracellular Mn, iron (Fe), and magnesium (Mg), supporting a role for MntE in Mn and Fe export and a role for Mg in offsetting Mn toxicity. Growth of the mntE mutant in excess Fe also results in increased levels of intracellular Fe, but not Mn or Mg, providing further support for MntE in Fe efflux. Inactivation of mntE in the presence of excess iron also results in the upregulation of glycerol catabolic genes and enhanced biofilm growth, and addition of glycerol is sufficient to augment biofilm growth for both the mntE mutant and its wild-type parental strain, demonstrating that glycerol availability significantly enhances biofilm formation. Finally, we show that mntE contributes to colonization of the antibiotic-treated mouse gastrointestinal (GI) tract, suggesting that E. faecalis encounters excess Mn in this niche. Collectively, these findings demonstrate that the manganese exporter MntE plays a crucial role in E. faecalis metal homeostasis and virulence.